The impacts of aflatoxin standards on health and nutrition in sub-Saharan Africa: The case of Kenya - Sirma, A.J.; Lindahl, Johanna F.; Makita, K.; Senerwa, D.; Mtimet, Nadhem; Kang’ethe, E.K.; Grace, Delia (Elsevier, 2018)
Human food and animal feed can contain many different hazards, which may be biological, chemical, or physical. In most countries, there are regulations that limit the levels of these hazards permitted in food and feed so as to protect consumers. Optimally, the levels specified in the standards should make the food safe enough for everyone to consume, and often this is done by carrying out a risk assessment, based on scientific evidence of the levels that can be considered safe and the amount of contaminated products consumed. However, for some substances, especially carcinogens, it is difficult to calculate how much is safe to consume and some groups of people, such as small children or pregnant women, may be more sensitive than the population at large. While imposition of standards is motivated by health benefits, standards also have costs. These include the costs of compliance and verification, which translate- into increased costs of purchase and reduction of the products available. In this paper we summarize current standards in sub-Saharan Africa related to aflatoxins, a priority hazard, and discuss their coherence and evidence-base. Next, using our recent research findings, we estimate the health risks of consuming foods contaminated with aflatoxins in Kenya. We also estimate the negative health and economic effects that would arise from strict application of different standards for aflatoxins. We discuss the results in light of health and nutrition goals.